Endolymphatic sac tumor: a rare neoplasm of the vestibular system - Vaidhyswaran, Roopak; Natarajan, Kiran; S., Raghu Nandhan; Vaidhyswaran, A. N.; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Endolymphatic sac tumors (ELSTs) are rare neoplasms originating from the endolymphatic sac, often associated with von Hippel-Lindau (VHL) disease. These tumors typically present with progressive hearing loss, vertigo, and vestibular symptoms, often mimicking Meniere’s disease. This case report discusses a 68-year-old female with a six-month history of progressive hearing loss and vertigo. Imaging revealed an ELST, and the patient underwent surgical resection via the translabyrinthine approach due to compromised hearing. Postoperatively, the patient underwent radiotherapy due to residual unresected tumor, stuck to posterior fossa dura and lying close to the ICA. A review of current literature on the diagnosis, treatment, and management strategies for ELSTs is also discussed.